Transformasi Hijau Balikpapan: Perencanaan RTH Strategis dengan Pendekatan IHBI - Pratiwi, Ratih; Putra, Muhammad Fauzan; Putri, Firda Nevira (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2024)
According to the Regulation of the Minister of Agrarian Af airs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 14 of 2022, Green Open Space (RTH) is defined as areas that function for plant growth, considering ecological aspects, water absorption, economic factors, socio-cultural elements, and aesthetics. In Balikpapan, a rapidly growing city, RTH plays a crucial role in addressing urban environmental challenges. The availability of RTH in Balikpapan is only about 12.92% of the city’s total area, far below the minimum target of 30% according to Law Number 26 of 2007. Additionally, regulations regarding the provision of RTH have not specified priority locations. Therefore, a thorough analysis is necessary to identify appropriate RTH locations. Utilizing the Indonesian Blue-Green Index (IHBI), this study employs both quantitative and descriptive analyses to determine the RTH needs. The analysis reveals an area of 825.7 hectares with a high demand for RTH